Tourism destination management: Strategies to implement green marketing in rural destinations - Santos, Marta Marinho Teodoro dos (2023)
The tourism industry has recently witnessed a surge in rural tourism, due to its ability to provide unique and personalized experiences. During the COVID pandemic, several rural accommodations (RA) saw an increase in bookings. This shift shows the need for identifying the factors that result in good RA experiences. Customer ratings are a possible way to assess customer satisfaction. However, research on the factors influencing ratings have remained relatively uncharted territory. We seek to conduct a detailed analysis of the factors that contribute to both high and low customer ratings in RAs. Using fsQCA as a research methodology, we have examined multiple RAs located in Portugal. We aim to identify types of clients, and the respective rural experiences they are looking for. Our study identified two configurations that result in high ratings. One configuration caters to clients looking for diverseness in experiences, products and services, while the other describes consumers looking for premium, pricy and sustainable experiences. For both, diverseness in bedroom choice was equality important. Three configurations were identified for low rating situations, with the absence of good bedroom choices and high prices being often present. These results can help management stay competitive in the RA development market.